Pollen limitation failing reproductive success in selected animal pollinated trees of tropical moist deciduous forest of north-eastern hill region, India - Khanduri, Vinod (Hacquetia, 2023)
The aim of this study was to estimate reproductive effort and success in tropical trees and to examine the effect of pollen limitation of reproductive success. Pollen limitation was assessed through pollen supplementation experiment in response to open pollination treament. The taxa selected were Bombax ceiba, Erythrina stricta (ornithophilous trees), Lagerstroemia speciosa, Mesua ferrea and Schima wallichii (entomophilous trees). Index of pollen limitation was maximum in Bombax ceiba and Erythrina stricta (both self - incompatible species). The remaining three species were partially self-incompatible with favouring selfing by Lagerstroemia speciosa and Mesua ferrea and supporting outcrossing by Schima wallichii. Therefore, the high index of pollen limitation in Bombax ceiba and Erythrina stricta might be due to the effect of either being lack of quality pollen or lack of bird pollinators. All five species produce a large amount of pollen at individual tree level in the order of 108 (Erythrina stricta) to 1010 (Mesua ferrea). Fruit and seed set following pollen supplementation were higher than the open pollination (as control) in all the study species. Pollen limitation was the result of limited pollen quantity and quality. Pollen limitation in this study is likely associated with the effectiveness of pollinator and their frequency, as all the studied species had produced ample pollen at tree crown level which ultimately leading to pollinator resource limitation in tropical trees.